Relationships between bronchoscopy, microbiology, and radiology in noncystic fibrosis bronchiectasis - Nursoy, Mustafa Atilla; Kılınç, Ayşe Ayzıt; Abdillahi, Fatouma Khalif; Ustabaş Kahraman, Feyza; Muhammed Al Shadfan, Lina; Sümbül, Bilge; Bilgin, Sabriye Şennur; Çakır, Fatma Betül; Daşkaya, Hayrettin; Çakır, Erkan (Mary Ann Liebert Inc., 2021)
Background: Published data on the correlations of bronchoscopy findings with microbiological, radiological, and pulmonary function test results in children with noncystic fibrosis (CF) bronchiectasis (BE) are unavailable. The aims of this study were to evaluate relationships between Bronchoscopic appearance and secretion scoring, microbiological growth, radiological severity level, and pulmonary function tests in patients with non-CF BE. Methods: Children with non-CF BE were identified and collected over a 6-year period. Their medical charts and radiologic and bronchoscopic notes were retrospectively reviewed. Results: The study population consisted of 54 female and 49 male patients with a mean age of 11.7 ± 3.4 years. In the classification according to the bronchoscopic secretion score, Grade I was found in 2, Grade II in 4, Grade III in 9, Grade IV in 17, Grade V in 25, and Grade VI in 46 patients. When evaluated according to the Bhalla scoring system, 45 patients had mild BE, 37 had moderate BE, and 21 had severe BE. Microbial growth was detected in bronchoalveolar lavage fluid from 50 of the patients. Forced expiratory volume in 1 s (FEV1) and functional vital capacity decreased with increasing bronchoscopic secretion grade (P = 0.048 and P = 0.04), respectively. The degree of radiological severity increased in parallel with the bronchoscopic secretion score (P = 0.007). However, no relationship was detected between microbiological growth rate and radiological findings (P = 0.403). Conclusions: This study showed that bronchoscopic evaluation and especially scoring of secretions correlate with severe clinical condition, decrease in pulmonary function test, worsening in radiology scores, and increase in microbiological bacterial load in patients. Flexible endoscopic bronchoscopy should be kept in mind in the initial evaluation of non-CF BE patients.
Keywords: Bronchiectasis; Bronchoscopy; Radiology